Implementasi strategi manajemen risiko dalam mengatasi non-performing financing pada perbankan syariah di masa pandemi Covid-19 - Maulida, Lutfia Uswatul (Maliki Interdisciplinary Journal, 2024)
This article aims to explain risk management strategies in overcoming Non-Performing Financing (NPF) in Sharia Commercial Banks during the Covid-19 pandemic. The research methodology uses a descriptive qualitative approach with data sources from internal documents of Bank Syariah Indonesia, direct interviews, as well as related literature and regulations. The research results show that financing risk management has two main aspects: based on Natural Certainty Contracts (NCC) and Natural Uncertainty Contracts (NUC). The risk management strategy implemented includes establishing a collection team, financing restructuring, insurance claims and collateral auctions. Financing restructuring is considered an effective way to overcome problematic financing and prevent losses for banks. By implementing effective risk management strategies, Sharia Commercial Banks can minimize losses and increase financial stability and customer trust